Characterization of Chestnut Behavior with Photosynthetic Traits - Gomes-Laranjo, José; Dinis, Lia-T.; Martins, Luís; Portela, Ester; Pinto, Teresa; Ara, Marta Ciordia; Díaz, Isabel Feito; Majada, Juan; Peixoto, Francisco; Lorenzo, S. Pereira; Cabrer, A.M. Ramos; Zhang, Changhe; et al. (IntechOpen, 2012)
None